Assessment of Anxiety Level Among Doctors and Paramedical Staff in a Tertiary Care Hospital, During COVID-19 Pandemic (Medical Forum Monthly, 2020)
Objective: To assess the level of anxiety among doctors and paramedical staff working in a tertiary care Hospital during COVID-19-Pandemic.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Abwa Hospital & Research Centre attached with Abwa Medical College, Faisalabad for the period of three months i.e. May, 2020 to July, 2020.Materials and Methods: Total 55 participants including 11 doctors & 44 paramedics serving specifically COVID-19 patients were selected to assess the level of anxiety and its associated factors.Results: out of total 55 participants, the level of anxiety was higher among medical doctors (mean score =6.91+7.0) as compared to paramedical staff (mean score3.25+4.68) where 31.7% of frontline health workers reported anxiety on BAI. 20 % (n=11) mild symptoms, a single worker only reported moderate anxiety &7.2% reported severe anxiety.Conclusion: During the pandemic of COVID-19 disease, among health care workers of ABWA hospital, medical doctors reported anxiety problems to a greater extent as compared to paramedical staff although intensity of anxiety was disproportionately higher in paramedical group. Considering this, there is a need of implementing programs of mental health being for health care professionals as an essential component of every epidemic at both national and international level.